A meta-analysis on the role of sonication in the diagnosis of cardiac implantable electronic device-related infections - Araújo, Daniela; Martins, João P.; Ferreira, Stephanie Lopes; Mota, Sandra; Ferreira, Pedro L.; Pimenta, Rui (Frontiers in Microbiology, 2024)
One of the biggest obstacles in diagnosing Implant-Associated Infections is the lack of infection criteria and standardized diagnostic methods. These infections present a wide range of symptoms, and their diagnosis can be hampered by the formation of microbial biofilms on the surface of implants.This study aimed to provide insight into the performance of sonication in the diagnosis of infections associated with Cardiac Implantable Electronic Devices, to help define a consensus on the algorithm for the microbial diagnosis of these infections.We carried out a systematic review with meta-analysis. The PRISMA methodology guidelines were followed, and an advanced search was carried out in PubMed and Web of Science, which enabled 8 articles to be included in the review, in which a meta-analysis was also carried out.QUADAS-2 was used to assess the risk of bias and effect measures were calculated to assess publication bias. The overall sensitivity of the method was 0.823 (95% CI: 0.682-0.910) and the specificity was 0.632 (95% CI: 0.506-0.743). These results suggest that sonication may offer advantages in diagnosing these infections. However, it is essential to approach these findings carefully and take into account the recommendations provided in the EHRA 2019 guidelines.This study highlights the importance of more effective diagnostic approaches for implantable medical device-associated infections to improve the quality of treatment and minimize the risks associated with these challenging medical conditions.